Cyber Threats Early Detection Countermesures and Benefits - Ambusaidi, Husam Hassan; Kumar, Dr Prakash (IJRDO -Journal of Computer Science Engineering, 2017)
In the recent years, the cyber-attacks have evolved and become more complex. The cyber-attacks have moved from random attacks to targeted and high sophisticated attacks. On a daily basis, companies and organizations are targeted by different and sophisticated cyber attacks. Many of these companies and organizations are unconscious that they are targeted by cyber threats and their networks are already compromised. Furthermore, vast majority of companies and organizations are vulnerable to various cyber threats. Hence, to detect the cyber threats and compromised networks at early stage the organizations need better mechanism for cyber threat detection. Several cyber security vendors have introduced advanced technologies to allow early detection of the cyber threats. This research will discuss the importance of early detection for cyber threats. Furthermore, the research study the current emerged cyber threats with relation to early detection. Further outcome, this paper research will identify the benefits of proactive security protection.